Urinary Tract Infection among Renal Transplant Recipients in Yemen - Gondos, A.S.; Al-Moyed, K.A.; Al-Robasi, A.B.A.; Al-Shamahy, H.A.; Alyousefi, N.A. (Public Library of Science, 2015)
Urinary tract infection (UTI) is the most common complication following kidney transplantation (KT), which could result in losing the graft. This study aims to identify the prevalence of bacterial UTI among KT recipients in Yemen and to determine the predisposing factors associated with post renal transplantation UTI. A cross sectional study included of 150 patients, who underwent KT was conducted between June 2010 and January 2011. A Morning mid-stream urine specimen was collected for culture and antibiotic susceptibility test from each recipient. Bacterial UTI was found in 50 patients (33.3%). The prevalence among females 40.3% was higher than males 29%. The UTI was higher in the age group between 41-50 years with a percentage of 28% and this result was statistically significant. Predisposing factors as diabetes mellitus, vesicoureteral reflux, neurogenic bladder and polycystic kidney showed significant association. High relative risks were found for polycystic kidney = 13.5 and neurogenic bladder = 13.5. The most prevalent bacteria to cause UTI was Escherichia coli represent 44%, followed by Staphylococcus saprophyticus 34%. Amikacin was the most effective antibiotic against gram-negative isolates while Ciprofloxacin was the most effective antibiotic against Staphylococcus saprophyticus. In conclusion, there is high prevalence of bacterial UTI among KT recipients in Yemen. Diabetes mellitus, vesicoureteral reflux, neurogenic bladder, polycystic kidney and calculi were the main predisposing factors.